Performance of Topological Perception in the Myopic Population. (1st November 2020) - Sun, Yi; Li, Fei; Li, Hao; Song, Yunhe; Wang, Wenbo; Zhou, Rouxi; Xiong, Jian; He, Wanbing; Peng, Yuying; Liu, Yuhong; Wang, Liping; Huang, Yan; et al.
ABSTRACT: Purpose : Discriminating objects' topological property (TP) is a primitive function of visual representation, which is reported to be associated with magnocellular (M) visual pathway, temporal lobe (TL), and superior colliculus (SC)-pulvinar subcortical pathway. Previous studies have shown that M pathway and TL were affected in high myopia (HM) subjects. The study was accordingly designed to explore whether topological perception performance was abnormal in HM subjects. Methods : 30 mildly myopic, 25 moderately myopic, 35 highly myopic, and 20 emmetropic subjects were enrolled. All participants underwent a comprehensive ophthalmological assessment including automated refraction, intraocular pressure, Humphrey 10–2 standard automated perimetry, ocular fundus photography and swept-source optical coherence tomography. Defined by differences in hole, TP and non-TP discrimination with letters "E", "S", "P", "d" as stimuli in the central and peripheral regions was performed using the MATLAB 2017 software. d-primes extracted from the software were analyzed within each group. The correlation of peripheral TP/non-TP deficit with spherical equivalent (SE), axial length (AL) and average peripapillary retinal nerve fiber layer (RNFL) thickness was performed. Results : The patterns of topological perception performance were similar among the groups. TP discrimination peripherally was significantly better than that centrally in the mild myopia ( P < .001), moderate myopia ( P < .001), high myopia ( P < .001) and emmetropia groups ( P = .001). In the peripheral region, TP d-prime scores were significantly better than non-TP d-prime scores (all P < .001). The main and interaction effects of eccentricity and stimulus type were statistically significant( P < .05). There was no statistically significant correlation between peripheral TP/non-TP deficit and SE, AL or average RNFL thickness ( P > .05). Conclusions : The current study first showed that patterns of topological perception among the myopic population were similar and not affected by the severity of myopia.